Reflection on the Austrian Newspaper Coverage of the Role and Relevance of Urban Open-and Green-Spaces in Vienna During the First COVID-19 Lockdown in 2020. - Gugerell, Katharina; Netsch, Stefan (Taylor & Francis, 2020)
The first lockdown in spring 2020 impacted greatly on Austrians’ daily lives and the general well-being, especially on urban dwellers. The country’s government forbade people to use public spaces, such as city squares or parks. Media were quick to pick up on the subject, which sparked debate on the importance and function of public green recreational spaces in national newspapers. This article maps and reflects on print news coverage of the role and relevance of urban open and green spaces during the first lockdown period in Austria in early spring 2020. The qualitative analysis of reports published in Austria’s leading newspapers showed that two topics were repeatedly covered: (i) the impact of being forced to live in a confined space on the well-being of urban dwellers after parks and public areas were closed; and (ii) functions of open spaces and the relevance of streetscapes in dense urban areas where parks are scarce. The results reveal the importance of public and green spaces for people’s physical and mental health, especially in challenging situations, such as lockdowns. Therefore, urban green spaces ought to be considered as one sector of the country’s critical infrastructure. Considering the way public spaces were dealt with during lockdown, the necessity for an in-depth discussion on and rethink of present urban planning, housing, retrofitting, and mobility practice becomes evident.
Keywords: Öffentlicher Raum; Freiraum; Grünraum; Nutzungseinschränkung; Presse; Berichterstattung; Auswertung; Inhaltsanalyse; Corona-Krise